2019
DOI: 10.1021/acsinfecdis.8b00351
|View full text |Cite
|
Sign up to set email alerts
|

5-Carboxytetramethylrhodamine-Ampicillin Fluorescence Anisotropy-Based Assay of Escherichia coli Penicillin-Binding Protein 2 Transpeptidase Inhibition

Abstract: The high-molecular mass penicillin-binding proteins (PBPs) are the essential targets of the β-lactam classes of antibacterial drugs. In the Gram-negative pathogen Escherichia coli, these include PBP1a, PBP1b, PBP2, and PBP3. Techniques that enable facile measurement of the potency of inhibition of these targets are valuable for understanding structure−activity relationships in programs aimed at discovering new antibiotics to combat drug-resistant infections. Continuous fluorescence anisotropy-based assays for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Inhibition of E. coli PBP2 was measured according to the method published in Shapiro et al . A set of 2-fold serial dilutions of each inhibitor from 61.44 to 0.06 and 0 μM were prepared from a fresh solution of the compound dissolved in assay buffer consisting of 0.1 M sodium phosphate (pH 6.0) and 0.01% Triton X-100.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of E. coli PBP2 was measured according to the method published in Shapiro et al . A set of 2-fold serial dilutions of each inhibitor from 61.44 to 0.06 and 0 μM were prepared from a fresh solution of the compound dissolved in assay buffer consisting of 0.1 M sodium phosphate (pH 6.0) and 0.01% Triton X-100.…”
Section: Methodsmentioning
confidence: 99%
“…The second-order inactivation rate constant k inact /K i was calculated from the set of progress curves using Global Kinetic Explorer (Kintek) as previously described. 13 Inhibition of E. coli PBP2 was measured according to the method published in Shapiro et al 38 A set of 2-fold serial dilutions of each inhibitor from 61.44 to 0.06 and 0 μM were prepared from a fresh solution of the compound dissolved in assay buffer consisting of 0.1 M sodium phosphate (pH 6.0) and 0.01% Triton X-100. Inhibitor solution (2 μL) and 2 μL of 90 nM 5-TAMRA-ampicillin were added to the wells of a low-volume, shallow-well, black polystyrene, 384-well microplate (Corning).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Kinetic parameters were calculated and analyzed using the Michaelis-Menten curve in GraphPad Prism 6 (GraphPad Software, La Jolla, CA, USA; www.graphpad.com ). The following wavelengths and extinction coefficients were used: tebipenem (Δε 297 = −9550 M −1 cm −1 ( 83 )); panipenem (Δε 297 = −7400 M −1 cm −1 ( 84 )); doripenem (Δε 296 = −7540 M −1 cm −1 ( 85 )); mecillinam (Δε 240 = −1100 M −1 cm −1 ( 86 )); imipenem (Δε 300 = −9000 M −1 cm −1 ( 87 )); meropenem (Δε 293 = −7600 M −1 cm −1 ( 87 )); biapenem (Δε 293 = −8630 M −1 cm −1 ( 87 )).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we report an optimized gel-based assay for the evaluation of 12 inhibitors in live, non-hypersusceptible E. coli MG1655. Historically, such assays have been carried out in vitro , using either pure proteins or cell lysates. , Results from these studies do not always translate to whole cells given the potential loss of native protein–protein interactions, as well as possible protein unfolding (i.e., the selectivity profile of a given inhibitor differs between live cells and lysates). Indeed, it has been demonstrated that Bocillin-FL labeling profiles in lysates are often missing some of the PBPs.…”
Section: Discussionmentioning
confidence: 99%